A PRELIMINARY INVESTIGATION OF POLYANILINE/CHITOSAN COMPOSITE’S PHYSICOCHEMICAL PROPERTIES AND POTENTIAL ELECTROCHEMICAL APPLICATION - NUR FARAHIN SUHAIMI; Siti Nor Atika Baharin; Nurul' Ain Jamion; Kavirajaa Pandian Sambasevam (Journal of Academia, 2022)
A polyaniline/chitosan (PANI/CHT) modified SPCE based sensor was developed and validated by electrochemical detection of PFOA. The PANI/CHT composite was synthesized by chemical oxidative polymerization technique. The synthesized material was characterized by scanning electron microscope (SEM)-Energy dispersive X-ray spectroscopy (EDX), Thermal gravimetric analysis (TGA) and Ultraviolet visible Spectroscopy (UV-Vis) techniques. The redox properties of the modified SPCE were examined by cyclic voltammetry studies. The investigation showed that PANI/CHT SPCE exhibit high electroactive surface area compared to unmodified SPCE. The PANI/CHT SPCE recorded lowest detection limit (LOD) of 1.60 ppb with LOQ of 4.82 ppb, in the linear range of 25-50 ppb.